Mechanical Mitral Valve Prosthesis Thrombosis: A Case Report - Pareikaitė, Viktorija; Makrickaitė, Silvija; Bakšytė, Giedrė (Acta medica Lituanica, 2025)
Background: A rare but serious complication of heart valve replacement, prosthetic valve thrombosis carries significant risks of morbidity and mortality. Effective management depends on prompt diagnosis and the appropriate treatment, often involving fibrinolytic agents. Protocols using slower infusion rates and lower doses of these agents have led to improved therapy outcomes.Clinical case: We report a case of a 56-year-old man admitted to the Lithuanian University of Health Sciences Kaunas Clinics due to mechanical mitral valve prosthesis thrombosis complicated by a respiratory failure and atrial fibrillation. The patient was treated with ultraslow thrombolysis with alteplase. The function of the mechanical valve prosthesis became normal, and the patient was discharged from the hospital.Discussion and Conclusions: Managing prosthetic valve thrombosis is challenging due to overlapping clinical features with other diagnoses and the lack of consensus on the treatment methods. Slow-infusion, low-dose thrombolytic therapy with alteplase can be a life-saving intervention with a high success rate.